THE ROLE OF INSURANCE IN INTERNATIONAL TRADE - Sohibjamol Abirkulova; Fazliddin Mukhammedov (Scholar Express Journals, 2024)
Foreign trade insurance plays a pivotal role in mitigating the inherent risks associated with international business transactions. This paper explores the various types of foreign trade insurance, examining their mechanisms, benefits, and limitations. It analyzes the impact of such insurance on global trade, highlighting its contribution to economic growth and stability. Furthermore, this article discusses the challenges and future trends in the foreign trade insurance market, emphasizing the importance of innovation and adaptation in an increasingly interconnected world.
Keywords: Foreign Trade Insurance; Credit Insurance; Political Risk Insurance